Perancangan Sistem Tata Udara dengan Software Bry-Air pada Ruang Kamar Tidur di Bogor, Indonesia - Soewono, Arka Dwinanda; Alferio, Gavin; Darmawan, Marten (Cylinder : Jurnal Ilmiah Teknik Mesin, 2023)
An effective and efficient air system can provide optimal comfort and health for room occupants. This research uses Bry-Air Software to design an integrated air conditioning system that can improve comfort and health by considering temperature, humidity, air circulation, and air cleanliness. The design was carried out for a bedroom measuring 3 m x 3 mx 3 m using ASHRAE standards where the ideal room temperature is in the range of 23 ± 2°C, relative humidity 55 ± 5%, and ideal airflow of 108 Cubic Meters per Hour (CMH). ISO class 8 requirements with a maximum particle number of 100,000 particles/ft3 for a particle size of 0.5 µm are also used as a criteria during the design process to ensure clean air for room occupants. Simulation results from Bry-Air Software in accordance with ASHRAE and ISO standards found that the room needs to be equipped with a single Air Conditioner (AC) units with a capacity of ½ PK each, 1 Dehumidifier unit with a capacity of 51 CMH and an Air Cleaner with Pre-Filter and Medium Filter. The results of this research hopefully can contribute to developing integrated air conditioning systems for the comfort and health of building occupants in Indonesia.